Impact of Application of Multifunction Electrode (MFE) Pads on Cardiopulmonary Resuscitation Quality - Radosław Zalewski; Mateusz Puślecki; Łukasz Szarpak; Tomasz Kłosiewicz; Marek Dąbrowski; Bartłomiej Perek (Emergency Medicine International)
Background. Early defibrillation and high-quality chest compressions are crucial in treatment of sudden cardiac arrest (SCA) subjects. The aim of this study was to assess an impact of defibrillation methods on cardiopulmonary resuscitation (CPR) quality. Methods. A randomized simulation cross-study was designed, in which 100 two-person paramedical teams participated. Two 10-minute scenarios of SCA in the mechanism of ventricular fibrillation were analysed. In the first one, teams had at their disposal defibrillator with hard paddles (group C), whereas in the second one, adhesive electrodes were used (group MFE). The CPR quality was evaluated on the basis of the chest compression parameters (rate, depth, recoil, compression fraction (CCF), and no-flow time), airways patency achievement, and successful emergency drug administration. Results. Substituting standard hard paddles with adhesive electrodes led to an increase in CCF (77% vs 73%; p<0.05), higher rate of complete chest recoil, and a decrease in no-flow time (6.0 ± 1.1 vs. 7.3 ± 1.1; p<0.001). The airway patency was ensured sooner in group MFE (271 ± 118 s vs. 322 ± 106 s in group C; p<0.001). All teams in scenario with adhesive electrodes were able to administer two doses of adrenaline, meanwhile only 74% of them in group C (p<0.001). Moreover, in 8% of group C scenarios, paramedics did not have enough time to administer amiodarone. Conclusion. Our simulation-based analysis revealed that use of adhesive electrodes during defibrillation instead of standard hard paddles may improve the quality of CPR performed by two-person emergency team.